1999
DOI: 10.1002/masy.19991370103
|View full text |Cite
|
Sign up to set email alerts
|

Polyelectrolytes bearing azobenzenes for the functionalization of multilayers

Abstract: SUMMARY: Thin polymeric films are assembled by the alternating adsorption of oppositely charged polyelectrolytes. The polyions are hctionalized by azobenzenes, typically carrying donor-acceptor substituents. The azobenzene chromophores are exploited as versatile analytical tools, to study the assembling process, and to control the f i l m quality. A high concentration of ionic groups does not seem to be advantageous per se for good film growth, but rather the matching of the charge densities of the polyelectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
70
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 49 publications
(74 citation statements)
references
References 50 publications
4
70
0
Order By: Relevance
“…The same is true for other rather hydrophobic polycations 130,135) . Therefore, we suggested that successful deposition asks for appropriate matching of the charge density of the used polyelectrolyte pair, rather than for a minimum charge density 135) . Of course, if one of the partners is a standard strong polyelectrolyte, the second polyion should have a high charge density, too, to favor film growth by ESA.…”
Section: Polymers Suited For Esasupporting
confidence: 55%
See 4 more Smart Citations
“…The same is true for other rather hydrophobic polycations 130,135) . Therefore, we suggested that successful deposition asks for appropriate matching of the charge density of the used polyelectrolyte pair, rather than for a minimum charge density 135) . Of course, if one of the partners is a standard strong polyelectrolyte, the second polyion should have a high charge density, too, to favor film growth by ESA.…”
Section: Polymers Suited For Esasupporting
confidence: 55%
“…Fortunately despite these and other 135) observations, the picture of the critical minimum charge density is oversimplified. A number of polymers have been successfully grown to films by ESA though bearing a surprisingly low density of charge 136,137) .…”
Section: Polymers Suited For Esamentioning
confidence: 91%
See 3 more Smart Citations